EKSISTENSI TRADISI BURDAH PADA MASYARAKAT DI KELURAHAN KELAYU UTARA LOMBOK TIMUR - Dini Nur Laili Apriani (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2020)
Talking about traditions, of course every country has its own traditions and every region in a country has different traditions. And of course the tradition is maintained and preserved properly so that it does not become extinct and can be recognized by the next generation. As in one of the villages in Selong District, East Lombok Regency, namely in North Kelayu Village, it still maintains and preserves the old tradition, namely the Burdah tradition. This research aims to; 1) knowing how the existence of the burdah tradition is maintained in the North Kelayu Village, 2) knowing the existence of the values contained in the burdah tradition in North Kelayu Village. This research is a type of qualitative research and uses a descriptive approach. Data collection techniques used are observation and interviews. While the data analysis procedures used are data reduction, triangulation, data presentation, and drawing conclusions. The results of this study indicate; 1) the existence of the burdah tradition in the North Kelayu Village is maintained with various efforts, including: first, doing routine exercises every 2 times a week, namely on Thursday nights and Sunday nights. Second, teach Burdah to future generations, such as youth and children. Third, Have a good membership structure, starting from the chairman, secretary, and treasurer. Fourth, have programs other than burdah readings, such as procedures for managing corpses, starting from how to bathe corpses to reading talkin. Fifth, every community has an understanding that the burdah tradition is a legacy from one of the Malay figures, namely TGH. Umar, so that it is still guarded and preserved. 2) the values contained in burdah, namely: First, social values, which is about a togetherness. Second, the value of worship, because reading burdah means we are praying to Allah swt. and pray to the Prophet Muhammad. which is an extraordinary worship. Third, cultural values, because the burdah was inherited by the first generation to be maintained and preserved by subsequent generations. From the results of this study, it can be concluded that the existence of burdah tradition is maintained by making various efforts. Then the values contained in the burdah tradition are social values, worship values, and cultural values.